Workshop dan Pelatihan Penerapan E-Learning (Learning Management System) Pada JPRMI di Era Milenial - Zuraidah, Eva; Eko Setia Budi; Ipin Sugiyarto; Besus Maulana; Dito Tri Ardana; Aprilia Dimas; Ghifary Rafy Pratama; Kenji Ferdian Santosa; Muhamad Irfan (JPM: Jurnal Pengabdian Masyarakat, 2024)
Karang Taruna is a social organization as a forum and means of developing every member of society who grows and develops on the basis of awareness and social responsibility from and for the community, especially the younger generation in the region, especially those engaged in social welfare business. Meanwhile, membership of the DKI Jakarta Mosque Youth and Youth Network (JPRMI), hereinafter referred to as the DKI Jakarta Mosque Youth and Youth Network (JPRMI), is every member of the community. Limited understanding regarding system management has not been optimized within the JPRMI management environment. The management system used is still manual for the JPRMI DKI Jakarta membership information system. Therefore, Nusa Mandiri University carries out Community Service in the form of Workshops and Training on the Application of E-Learning (Learning Management System) in the Millennial era at JPRMI DKI Jakarta. With this training, it can help DKI Jakarta Mosque Youth and Teenagers (JPRMI) in managing and providing information data with training in implementing the e-learning management system